A retrospective medical records review of risk factors for the development of respiratory tract secretions (death rattle) in the dying patient. (22nd June 2018) - Kolb, Hildegard; Snowden, Austyn; Stevens, Elaine; Atherton, Iain
Abstract: Aim: Identification of risk factors predicting the development of death rattle. Background: Respiratory tract secretions, often called death rattle, are among the most common symptoms in dying patients around the world. It is unknown whether death rattle causes distress in patients, but it has been globally reported that distress levels can be high in family members. Although there is a poor evidence base, treatment with antimuscarinic medication is standard practice worldwide and prompt intervention is recognized as crucial for effectiveness. The identification of risk factors for the development of death rattle would allow for targeted interventions. Design: A case–control study was designed to retrospectively review two hundred consecutive medical records of mainly cancer patients who died in a hospice inpatient setting between 2009–2011. Fifteen potential risk factors including the original factors weight, smoking, final opioid dose and final midazolam dose were investigated. Methods: Binary logistic regression to identify risk factors for death rattle development. Results: Univariate analysis showed death rattle was significantly associated with final Midazolam doses and final opioid doses, length of dying phase and anticholinergic drug load in the pre‐terminal phase. In the final logistic regression model only Midazolam was statistically significant and only at final doses of 20 mg/24 hrs or over (OR 3.81 CI 1.41–10.34). Conclusions: Dying patients with a requirement for a high dose of Midazolam have an increased likelihood of developing death rattle.